Large impact of low concentration oxidized LDL on angiogenic potential of human endothelial cells: a microarray study. - Magomed Khaidakov; Sona Mitra; Xianwei Wang; Zufeng Ding; Nalini Bora; Valery Lyzogubov; Francesco Romeo; Steven A Schichman; Jawahar L Mehta (PLoS ONE, 2012)
Oxidized LDL (ox-LDL) is a key factor in atherogenesis. It is taken up by endothelial cells primarily by ox-LDL receptor-1 (LOX-1). To elucidate transcriptional responses, we performed microarray analysis on human coronary artery endothelial cells (HCAECs) exposed to small physiologic concentration of ox-LDL- 5 µg/ml for 2 and 12 hours. At 12 hours, cultures treated with ox-LDL exhibited broad shifts in transcriptional activity involving almost 1500 genes (>1.5 fold difference, p<0.05). Resulting transcriptome was enriched for genes associated with cell adhesion (p<0.002), angiogenesis (p<0.0002) and migration (p<0.006). Quantitative PCR analysis revealed that LOX-1 expression in HCAECs is at least an order of magnitude greater than the expression of other major ox-LDL specific receptors CD36 and MSR1. In keeping with the data on LOX-1 expression, pre-treatment of HCAECs with LOX-1 neutralizing antibody resulted in across-the-board inhibition of cellular response to ox-LDL. Ox-LDL upregulated a number of pro-angiogenic genes including multiple receptors, ligands and transcription factors and altered the expression of a number of genes implicated in both stimulation and inhibition of apoptosis. From a functional standpoint, physiologic concentrations of ox-LDL stimulated tube formation and inhibited susceptibility to apoptosis in HCAECs. In addition, ox-LDL exposure resulted in upregulation of miR-1974, miR-1978 and miR-21 accompanied with significant over-presentation of their target genes in the downregulated portion of ox-LDL transcriptome. Our observations indicate that ox-LDL at physiologic concentrations induces broad transcriptional responses which are mediated by LOX-1, and are, in part, shaped by ox-LDL-dependent miRNAs. We also suggest that angiogenic effects of ox-LDL are partially based on upregulation of several receptors that render cells hypersensitive to angiogenic stimuli.